Trend Fashion Hijab Bagi Generasi Milenial Terhadap Konsep Diri - emawati (Pusat Studi Gender dan Anak, 2020)
This Study aims to determine the trend of millenial generation hijab fashion in the squard girl community towards self-concept. This study aims to determine the trend of millenial generation hijab fashion in the squard girl community towards self-concept. The research instrument used was the observation sheet. By using a percentage test formula. Based on the result of self-concept research with indicators of sosial behavior that is equal to 90% easy to get along with group members, amounting to 100% respecting decisions in the group and by 75% good commucation with the group. With the overall recapitulation result of 89.58% showing very high criteria for self-concept. Thus the hijab fashion trend for millenial provides a positive response to self-concept